SYNTHESIS AND CHARACTERIZATION OF CERAMIC METAL Ni-YSZ PREPARED FROM LOCAL ZIRCON SAND AT VARIOUS Ni:YSZ COMPOSITION - Karima Apriany; Fitria Rahmawati; Eddy Heraldy; Dani G Syarif; Syoni Soepriyanto (ALCHEMY Jurnal Penelitian Kimia, 2017)
This research synthesized a cermet Ni-YSZ, in which the YSZ (yttria stabilized-zirconia) was synthesized from the local zircon sand, ZrSiO4, as a side product of tin mining plant in Bangka island, Indonesia. The synthesized YSZ in this research is zirconia, ZrO2 doped by 8 % mol of yttrium dioxide. The synthesis used solid state reaction method and the result was characterized its crystal structure and its cell parameters by XRD analysis equipped with Le Bail refinement, surface morphology analysis, and an impedance analysis to understand its ionic conductivity. The cermet Ni-YSZ was synthesized at a various composition of Ni:YSZ i.e., 20:80, 30:70, and 40:60 (b/b). The analysis shows that Ni-YSZ is in two phases of Ni and YSZ without any presence of a third phase. It indicates that there was no solid state reaction between Ni and YSZ during synthesis. In this Ni-YSZ cermet, the Ni phase in a cubic structure, and the YSZ is also in a cubic structure. Morphological study shows that the addition of Ni to YSZ allows the morphology to become more roughness with larger grain size. This research found that the Ni-YSZ 20:80 has highest ionic conductivity.